Enhancing the Photovoltaic Performance of Cu2ZnSn(S, Se)4 Solar Cells with Ba Trace Doping: Large Chemical Mismatch Cation Incorporation. Issue 11 (24th September 2021) - Guo, Jiajia; Mao, Yang; Zhang, Zhaojing; Ao, Jianping; Gao, Qing; Han, Yanchen; Cao, Chun; Wang, Weihuang; Liu, Fangfang; Liu, Wei; Zhang, Yi
Abstract : Being absent from larger mismatch of ionic radius and chemical coordination between the cations in Cu2 ZnSn(S, Se)4 (CZTSSe) can aggravate the formation of detrimental cation antisite defects and clusters with low formation energy, which results in a serious open‐circuit voltage deficit and a challenge for higher power conversion efficiency of CZTSSe solar cells. External cation doping or alloying is a more effective strategy to solve this issue. Herein, samples of trace Ba doping into CZTSSe are fabricated by the sol–gel method and the mechanism of such trace Ba doping are studied combined by X‐ray diffraction (XRD), Raman, and photoluminescence (PL) measurements. The performance of CZTSSe solar cells is increased by 25.7% as 1% Ba is doped into CZTSSe to substitute Zn. The results highlight the roles of the trace Ba doping on the performance of CZTSSe solar cells, which is beneficial to the reduced formation of the detrimental defects and associated clusters. As a consequence, the bandgap fluctuations are reduced, which results in the improvement of V OC and thus the performance of the solar cell. The cation substitution engineering with larger chemical mismatched alkaline‐earth metal cations provides insights for further improvement of CZTSSe solar cells based on earth abundant elements. Abstract : The band‐tailing and bandgap fluctuations in CZTSSe solar cells can be reduced through partially substituting Zn with trace Ba doping. When the doping ratio of Ba in CZTSSe is only 1%, the power conversion efficiency of the CZTSSe solar cells is noteworthily enhanced by 25.6%, due to the doping cation with large difference of the chemical coordination environment.